2021
DOI: 10.1016/j.artd.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Perioperative Laboratory Tests in Total Hip and Knee Arthroplasty: Are They Necessary for All Patients?

Abstract: Background: Laboratory studies are routinely obtained preoperatively and postoperatively for total hip arthroplasty (THA) and total knee arthroplasty (TKA). This study evaluates the necessity of routine, perioperative laboratory tests and identifies risk factors for laboratory-associated interventions. Methods: This retrospective review evaluated 967 consecutive patients scheduled for primary, unilateral TKAs (n ¼ 593) or THAs (n ¼ 374) over an 18-month period at a single institution. Preoperative prothrombin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Angerame et al concluded that medical comorbidities and abnormal preoperative lab tests should guide the decision to obtain postoperative lab testing. 3 However, their conclusion was solely based on whether abnormal labs led to actionable medical interventions. Hence, their study does acknowledge that abnormal preoperative labs can still predict adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Angerame et al concluded that medical comorbidities and abnormal preoperative lab tests should guide the decision to obtain postoperative lab testing. 3 However, their conclusion was solely based on whether abnormal labs led to actionable medical interventions. Hence, their study does acknowledge that abnormal preoperative labs can still predict adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found specific comorbidities that could also guide postoperative blood tests. 35 The routine use of postoperative blood tests is a significant financial burden to healthcare providers, 36 and previous studies have suggested that this is not a cost-effective practice. 37 It is also essential that patients with these risk factors be managed and optimized preoperatively to avoid postoperative interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The study included preoperative neutrophil, monocyte, total lymphocyte, leukocyte, and platelet counts; albumin level; albuminglobulin ratio (A/G ratio); hemoglobin level; and HbA1c. These values are commonly utilized as screening metrics for patients undergoing TJA and have previously been identified as predictors of postoperative complications following TJA [21][22][23][24]26,27,[43][44][45][46][47][48][49][50][51][52] . The NLR, MLR, PLR, and SII were included to investigate their preoperative utility to predict PJI due to their proven function as diagnostic markers of PJI and as preoperative predictors of complications in other surgical specialties [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] .…”
Section: Identification Of Predictive Preoperative Laboratory Valuesmentioning
confidence: 99%
“…Preoperative risk stratification and medical optimization remain paramount to mitigate the risk of complications in this high-risk population. Preoperative laboratory values, including a complete blood-cell count (CBC) and albumin level, are routinely obtained and have demonstrated utility in predicting complications following total joint arthroplasty (TJA) [21][22][23][24][25][26][27] . Additionally, there is a growing interest in CBC-based ratios (CBRs), including the platelet-lymphocyte ratio (PLR), neutrophillymphocyte ratio (NLR), monocyte-lymphocyte ratio (MLR), and systemic immune-inflammation index (SII), which serve as markers of systemic inflammation.…”
mentioning
confidence: 99%